Assessment of oral health status and quality of life in hearing-impaired children from Syria - Alemar Nazeeh Ghannam; Mayssoon Dashash; Louei Darjazini Nahhas (Nature Publishing Group, 2024)
Abstract Aim This study aimed to evaluate the oral health status of children with hearing impairments and assess the relationship between various oral health factors and the Pediatric Oral Health-Related Quality of Life. Materials and methods This observational cohort study involved 90 hearing-impaired children aged 6-12 years. Diagnostic tools such as pure-tone audiometry were used to evaluate their hearing abilities. Dental health was assessed by calculating DMFT, dmft, Plaque and Gingival indices. The oral health-related quality of life was measured using the POHRQoL. Results The severity of hearing impairment varied with 3% having severe hearing loss, 13% having profound hearing loss, and 83% having complete hearing loss. A high prevalence of dental cavities with 93% of children affected was found. DMFT score was similar between males and females (2.5 ± 0.3 vs. 2.3 ± 0.3 respectively). Males exhibited a higher mean dmft score (4.1 ± 0.5 vs. 3.3 ± 0.5), and a higher mean Plaque Index (1.9 ± 0.1 vs. 1.5 ± 0.1). On the other hand, females showed a higher mean Gingival Index (0.9 ± 0.1 vs. 1.1 ± 0.2). Results indicated a decreased OHRQoL with a mean POQL score of 6.4 ± 2.89. Spearman's test revealed a significant positive correlation between POQL total score and DMFT scores (P = 0.000), dmft scores (P = 0.000), Plaque Index scores (P = 0.000), and Gingival Index scores (P = 0.038). There was a weak positive correlation between hearing impairment severity and POQL total score, it was not statistically significant. Conclusions Children who have hearing impairments exhibit poor oral health, and levels of dental caries, which can negatively impact their overall POHRQoL. Therefore, it is highly recommended to start specialized oral health education and comprehensive dental care programs to improve their OHRQoL.